Covalent Organic Frameworks Composites Containing Bipyridine Metal Complex for Oxygen Evolution and Methane Conversion - Xin Liu; Lijuan Feng; Yongpeng Li; Tian Xia; Zhuyin Sui; Qi Chen (Molecules, 2022)
Novel covalent organic framework (COF) composites containing a bipyridine multimetal complex were designed and obtained via the coordination interaction between bipyridine groups and metal ions. The obtained Pt and polyoxometalate (POM)–loaded COF complex (POM–Pt@COF–TB) exhibited excellent oxidation of methane. In addition, the resultant Co/Fe–based COF composites achieved great performance in an electrocatalytic oxygen evolution reaction (OER). Compared with Co–modified COFs (Co@COF–TB), the optimized bimetallic modified COF composites (Co0.75Fe0.25@COF–TB) exhibited great performance for electrocatalytic OER activity, showing a lower overpotential of 331 mV at 10 mA cm−2. Meanwhile, Co0.75Fe0.25@COF–TB also possessed a great turnover frequency (TOF) value (0.119 s−1) at the overpotential of 330 mV, which exhibited high efficiency in the utilization of metal atoms and was better than that of many reported COF-based OER electrocatalysts. This work provides a new perspective for the future coordination of COFs with bimetallic or polymetallic ions, and broadens the application of COFs in methane conversion and electrocatalytic oxygen evolution.